PEMAKAIAN REGISTER BAHASA KRU BUS AKAP DI TERMINAL TIRTONADI SURAKARTA (Kajian Sosiolinguistik) - Elen Inderasari; wahyu oktavia (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2018)
Abstract: The research entitled “Pattern Register Language Bus Crews Inter City Inter Provincial (AKAP) at Terminal Tirtonadi Surakarta” aims to describe the form of the registers of the inter-provincial city bus crew in the Tirtonadi Terminal of Surakarta, patterns of language variations caused by social factors one of which registers, and the emergence of the frequent register of the bus crew. Register becomes something very interesting to be examined in terminal Tirtonadi, because often social communication language. The type of research used is descriptive qualitative method by doing observation directly and place is not bound. The results of the study showed 50 word register findings that were classified according to the register form, the bus crew language register pattern, the creation of new words with different meanings and special words in the community between bus crews.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan wujud register bahasa kru bus Antar Kota Antar Provinsi (AKAP) di Terminal Tirtonadi Surakarta, pola variasi-variasi bahasa yang disebabkan karena faktor sosial salah satunya register, dan kemunculan register yang sering dipakai kru bus. Register menjadi sesuatu yang sangat menarik untuk diteliti di Terminal Tirtonadi karena seringnya komunikasi sosial yang dimunculkan dengan menggunakan pola bahasa komunikasi khusus. Metode penelitian yang digunakan adalah metode kualitatif deskriptif dengan melakukan observasi secara langsung dan tempat tidak terikat. Hasil penelitian menunjukkan 50 temuan kata register yang diklasifikasi berdasarkan wujud register, pola register bahasa kru bus, penciptaan kata baru dengan makna yang berbeda dan kata khusus dalam komunitas antar kru bus.